Terapi Yoga dan Penurunan Kadar Glukosa Darah pada Pasien DMT2 di Takalar - Suardi; Ernawati; Dina Oktaviana; Ipha Wahyuni Putri; Patmawati (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2026)
Background: Diabetes mellitus is a metabolic disorder characterized by impaired insulin secretion and/or action due to pancreatic beta-cell dysfunction and insulin resistance. This condition causes uncontrolled elevation of blood glucose levels. One nonpharmacological approach to diabetes management is yoga therapy. Objective: This study aimed to analyze the effect of yoga therapy on reducing blood glucose levels in patients with type 2 diabetes mellitus (T2DM). Methods: This study used a pre-experimental one-group pretest-posttest design without a control group. A total of 30 respondents were selected using purposive sampling. The inclusion criteria were patients with T2DM aged ≥ 45 years, blood glucose levels ≥ 200 mg/dL, willingness to participate, ability to follow yoga therapy, and absence of severe physical disorders. The exclusion criteria included noncompliance with therapy and clinical conditions that could endanger respondents during yoga. Blood glucose levels were measured using an Autocheck device. Data were analyzed using a paired t-test. Results: There was a significant difference in blood glucose levels before and after yoga therapy (p < 0.001). The mean blood glucose level decreased from 265.23 mg/dL to 207.60 mg/dL in the final week. Conclusion: Yoga therapy reduced blood glucose levels among patients with T2DM at Bulukunyi Community Health Center, Takalar Regency. Keywords: community health center, nonpharmacological intervention, random blood glucose, T2DM, yoga therapy